2018
DOI: 10.4108/eai.29-1-2021.168537
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Engineering Methods of Upgrading the Quality of Induction Traction Electric Motors

Abstract: The results of research on the creation of induction traction electric motors (EM), which made it possible to improve their technical, environmental and operational qualities, are presented. The main criterion for assessing the quality of EM were selected vibration levels. The main research methods were experimental and statistical methods. New technologies for assembling bearing units assemblies and EM as a whole were studied. New design and technological solutions have been developed. The dynamic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The criterion for evaluating the quality of such electric motors is the classes of permissible vibration in the frequency range from 5 Hz to 10 kHz (Figure 2). 25,26 Vibration levels exceeding acceptable values are diagnostic signs of reduced reliability and service life of the traction electric motor, proportional to the amount of exceeding permissible vibrations.
Figure 2.Ranges of vibration classes of electric motors.
…”
Section: Improving Evaluation Methods For Traction Electric Motorsmentioning
confidence: 99%
“…The criterion for evaluating the quality of such electric motors is the classes of permissible vibration in the frequency range from 5 Hz to 10 kHz (Figure 2). 25,26 Vibration levels exceeding acceptable values are diagnostic signs of reduced reliability and service life of the traction electric motor, proportional to the amount of exceeding permissible vibrations.
Figure 2.Ranges of vibration classes of electric motors.
…”
Section: Improving Evaluation Methods For Traction Electric Motorsmentioning
confidence: 99%
“…The study showed that such an implementation is viable in terms of cost and energy efficiency. The use of a Induction Motor (IM) instead of an internal combustion engine [6,7] with approximately the same power increases the traction force by approximately 2 times.…”
Section: Research Status Of Electric Tractor Designsmentioning
confidence: 99%
“…Зниження рівнів вібрації ЕД дозволяє підвищити їх безвідмовність, довговічність, ресурс, зменшити шкідливий вплив на людину і навколишнє середовище, знизити витрати на технічне обслуговування електромобілів в цілому [14].…”
Section: аналіз публікаційunclassified